A simmering dispute. (Economist, 1998)
Reports on legal battles between Sun Microsystems and Microsoft over the Java computer language. Details of Sun's suit against Microsoft, claiming that the software giant violated a licensing agreement by creating a version of Java that will run only on Windows-based personal computers; Microsoft's countersuit claiming that Sun itself broke the contract by introducing a new Java dialect that does not work as well as the old.